Iowa Birdline update, October 2, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for October 2, 1989. Highlights include reports of migrants of all sizes. Sightings include Sharp-tailed Sparrows, a Golden Eagle and Black-bellied Plovers. Epson - sheet feed/flatbed